Cutaneous Squamous Cell Carcinoma: Clinico-Dermoscopic and Histological Correlation: About 72 Cases - Sara El-Ammari; Sara Elloudi; Hanane Baybay; Meryem Soughi; Zakia Douhi; Fatima Zahra Mernissi; Mohammed Omari; Samira El fakir; Layla Tahiri (Mattioli1885, 2024)
Introduction: Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer. It represents 20% of malignant skin tumors. Dermoscopy is a very useful tool for its diagnosis, which is confirmed by anatomo-pathological study. Objective: to describe the different dermoscopic structures of cSCC and to investigate their association with clinical form and histopathological grade of differentiation. Methods: Retro-prospective epidemiological study, collecting patients with squamous cell carcinoma over a period of 5 years. We divided our study population into two groups according to the degree of histological differentiation (well-differentiated and non-well-differentiated) and according to the clinical form (nodulo-ulcerative and nodular) and compared different dermoscopic parameters between these two groups. Results: Of 72 invasive cSCC, 81.9% were well-differentiated and 18.1% were non-well- differentiated, the clinical form of cSCC was nodulo-ulcerative in 83.3% and nodular in 16.7%. The well-differentiated tumors showed dotted, glomerular and hairpin vessels and the predominance of a white pattern made of centrally distributed keratin as well as white circles, whitish perivascular halo, the distribution of these white structures was radial in nodulo-ulcerarive lesions in contrast to nodular lesions where their distribution as well as that of the keratin was rather diffuse. Non-well-differentiated tumors showed a combined white-red pattern with the predominance of arborizing vessels. Conclusion:Our results show that dermoscopy can be considered a reliable tool to distinguish between well- and poorly differentiated cSCC, the transition from one to the other is represented by an increase in the amount of mostly arborizing vessels and the decrease in white structures.